Asymmetric extractions in orthodontics - Melgaço,Camilo Aquino (2012)
INTRODUCTION: Extraction decisions are extremely important in during treatment planning. In addition to the extraction decision orthodontists have to choose what tooth should be extracted for the best solution of the problem and the esthetic/functional benefit of the patient. OBJECTIVE: This article aims at reviewing the literature relating the advantages, disadvantages and clinical implications of asymmetric extractions to orthodontics. METHODS: Keywords were selected in English and Portuguese and the EndNote 9 program was used for data base search in PubMed, Web of Science (WSc) and LILACS. The selected articles were case reports, original articles and prospective or retrospective case-control studies concerning asymmetrical extractions of permanent teeth for the treatment of malocclusions. CONCLUSION: According to the literature reviewed asymmetric extractions can make some specific treatment mechanics easier. Cases finished with first permanent molars in Class II or III relationship in one or both sides seem not to cause esthetic or functional problems. However, diagnosis knowledge and mechanics control are essential for treatment success.